Effects of multicomponent exercise nursing intervention in elderly stroke patients with frailty: a randomized controlled trial - Luo, Yanfang; Hao, Jianru; Zhu, Lingyun; Huang, Yujuan; Liu, Zhimin; Chen, Yuping; Qiu, Yuyu; Su, Zhenzhen; Sun, Renjuan (Frontiers in Medicine, 2024)
This study examines how multicomponent exercise nursing interventions affect the state of frailty, daily activities, and quality of life in elderly stroke patients with frailty. A total of 125 elderly stroke patients with frailty were randomly assigned to either a control group (n = 62) or an intervention group (n = 63). The control group received standard nursing care, while the intervention group received a multicomponent exercise nursing intervention in addition to standard care. Patients were assessed using the FRAIL Frailty Scale, Modified Barthel Index (MBI), and Short Form Health Survey (SF-36) before the intervention, 4 weeks after the intervention, and 12 weeks after the intervention. Significant differences were observed between the two groups in terms of frailty status, activities of daily living, and quality of life (p < 0.05). The intervention group had lower scores on the FRAIL Frailty Scale and higher scores on the MBI and SF-36 compared to the control group at both 4 and 12 weeks after the intervention (p < 0.05). These findings suggest that multicomponent exercise nursing interventions can effectively reduce frailty and improve activities of daily living and quality of life in elderly stroke patients with frailty.